2009
DOI: 10.1016/j.bbabio.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations in five patients with mitochondrial encephalomyopathy

Abstract: MELAS, MERRF, LHON and NARP, are well-established mitochondrial syndromes associated with specific point mutations of mitochondrial DNA (mtDNA). However, these recurrent mtDNA mutations account for only a minority of mitochondrial disease cases. To evaluate the impact of novel mtDNA mutations, we performed mtDNA sequence analysis in muscle and other tissues of 240 patients with different mitochondrial neuromuscular syndromes. We identified a total of 33 subjects with novel, private or uncommon mutations. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 54 publications
5
78
1
Order By: Relevance
“…The T10191C mutation, detected in patient 2 in this study, was first reported in a patient that presented with a progressive Leigh-like clinical picture of epilepsy, strokes, optic atrophy and cognitive decline by Taylor et al 32 Subsequently, several MELAS or LS patients were reported carrying the T10191C mutation. 31,[33][34][35] The clinical features of patient 2 in the present study conformed with typical MELAS but her brain MRI showed lesions in both cerebral cortex and midbrain, suggesting that a diagnosis of MELAS/LS overlap syndrome was more appropriate. Patient 3 presented a similar clinical picture as patient 2, with a final diagnosis of MELAS/LS overlap syndrome based on the combination of clinical manifestations and brain MRI findings.…”
Section: Discussionsupporting
confidence: 63%
“…The T10191C mutation, detected in patient 2 in this study, was first reported in a patient that presented with a progressive Leigh-like clinical picture of epilepsy, strokes, optic atrophy and cognitive decline by Taylor et al 32 Subsequently, several MELAS or LS patients were reported carrying the T10191C mutation. 31,[33][34][35] The clinical features of patient 2 in the present study conformed with typical MELAS but her brain MRI showed lesions in both cerebral cortex and midbrain, suggesting that a diagnosis of MELAS/LS overlap syndrome was more appropriate. Patient 3 presented a similar clinical picture as patient 2, with a final diagnosis of MELAS/LS overlap syndrome based on the combination of clinical manifestations and brain MRI findings.…”
Section: Discussionsupporting
confidence: 63%
“…Recombination of the iron-coordinated sulfur leads to formation of a cyclic-peroxo intermediate [5]. Homolytic cleavage of the O-O bond results in a sulfoxy-cation and an Fe(II)-activated oxygen [6]. Recombination [7] followed by hydrolysis yields the products, sulfite and GSH [8], and restore the enzyme to its resting state [1].…”
Section: Methodsmentioning
confidence: 99%
“…The latter, via resonance, gives a radical cation character to the coordinated sulfane sulfur on the substrate [4]. Recombination of the superoxo and sulfur radical species yields a cyclic peroxo intermediate [5], followed by homolytic cleavage of the O-O bond resulting in a sulfoxy-cation intermediate and an Fe(II)-bound activated oxygen [6]. Recombination of the activated oxygen and the sulfoxy-cation yields the GSSO 2 -intermediate [7], which is hydrolyzed to give the products, sulfite and GSH [8].…”
Section: Gssh + O + H O → Gsh + Somentioning
confidence: 99%
See 2 more Smart Citations